Democracy a case study - Moss, David A. 1964- (The Belknap Press of Harvard University Press, 2017)
Historian David Moss adapts the case study method made famous by Harvard Business School to revitalize our conversations about governance and democracy and show how the United States has often thrived on political conflict. These 19 cases ask us to weigh choices and consequences, wrestle with momentous decisions, and come to our own conclusions....